Hoarding versus circulation of wealth from the perspective of Maqasid Al-Shari'ah - Ibrahim, Ahmad Asad; Elatrash, Radwan Jamal Yousef; Farooq, Mohammad Omar (Emerald Group Publishing Limited, 2014)
Purpose - The purpose of the paper is to explore the issue of hoarding and dishoarding in modern context, especially as it relates to circulation of wealth, an important economic objective from Islamic viewpoint.